2021
DOI: 10.1097/txd.0000000000001219
|View full text |Cite
|
Sign up to set email alerts
|

Living Donor Versus Deceased Donor Pediatric Liver Transplantation: A Systematic Review and Meta-analysis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 56 publications
6
39
0
Order By: Relevance
“…27 The same study showed that LDLT recipients had a higher PELD score than DDLT recipients, echoing what we observed in the current study, where PELD score of maternal-LLD recipients is higher compared to DDLT recipeints. 27 The reduced likelihood of ACR in LDLT recipients was also described in the recent study by Przybyszewski et al, where multivariable analysis showed that LDLT was associated with a significantly lower risk of ACR (HR 0.53). 28 However, this study also described a lower incidence of ACR in maternal liver graft recipients when compared to paternal liver graft recipients, which was not supported by our findings.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…27 The same study showed that LDLT recipients had a higher PELD score than DDLT recipients, echoing what we observed in the current study, where PELD score of maternal-LLD recipients is higher compared to DDLT recipeints. 27 The reduced likelihood of ACR in LDLT recipients was also described in the recent study by Przybyszewski et al, where multivariable analysis showed that LDLT was associated with a significantly lower risk of ACR (HR 0.53). 28 However, this study also described a lower incidence of ACR in maternal liver graft recipients when compared to paternal liver graft recipients, which was not supported by our findings.…”
Section: Discussionsupporting
confidence: 89%
“…This is congruent with a previous multicenter study of pediatric LT recipients that reported that the percentage of children free of rejection in the first year post‐LT was higher in LDLT than DDLT recipients, regardless of their PELD/MELD score 9 . Our recent meta‐analysis comparing pediatric LDLT versus DDLT recipients showed that the odds ratio for ACR in LDLT recipients was almost half of that of DDLT recipients (OR 0.66, 95% CI 0.45–0.96, p = 0.03) 27 . The same study showed that LDLT recipients had a higher PELD score than DDLT recipients, echoing what we observed in the current study, where PELD score of maternal‐LLD recipients is higher compared to DDLT recipeints 27 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…With respect to LDLT, we could additionally show better graft and patient survival in recipients of LDLT, with recent 1-year patient survival rates of 92%. This is no novelty and has been described previously; however, our results encourage the option for LDLT, if available [30][31][32].…”
Section: Discussionsupporting
confidence: 70%
“…Three different reports by three different working groups have demonstrated almost zero survival of patients who have this histological subtype [74][75][76] . Under this prism, many symposia have been held to create an international consensus for the classification of these tumors [77] , and thus future research should also focus on evaluating the outcomes of children with hepatoblastoma by histologic subtype.…”
Section: Development Of New Biomarkers and Future Directionsmentioning
confidence: 99%